Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/nu11102295
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D and Total Cancer Incidence and Mortality: A Meta-Analysis of Prospective Cohort Studies

Abstract: Epidemiological studies have suggested inconclusive associations between 25-hydroxyvitamin D and total cancer incidence and mortality. The aim of this study was to quantitatively assess these associations by combining results from prospective cohort studies. A systematic literature search was implemented in PubMed and Scopus databases in April 2019. Comparing the highest with the lowest categories, the multivariate-adjusted relative risks (RRs) and the corresponding 95% confidence intervals (CIs) were pooled u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 59 publications
0
58
1
Order By: Relevance
“…In this post hoc analysis of the AMATERASU trial, daily supplementation with 2000 IU of vitamin D significantly improved 5 year RFS in the subgroup of patients with low bioavailable 25(OH)D levels, but not in the subgroup with high bioavailable 25(OH)D levels. In our previous analysis of the AMATERASU trial, vitamin D was not effective in the subgroup of patients with low serum levels (<20 ng/mL) of total 25(OH)D at baseline, contrary to our expectation that vitamin D would be effective only in the subgroup with low total 25(OH)D [4]. However, in this post hoc study, we demonstrated that vitamin D supplementation may be effective only in cancer patients with low bioavailable 25(OH)D levels.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In this post hoc analysis of the AMATERASU trial, daily supplementation with 2000 IU of vitamin D significantly improved 5 year RFS in the subgroup of patients with low bioavailable 25(OH)D levels, but not in the subgroup with high bioavailable 25(OH)D levels. In our previous analysis of the AMATERASU trial, vitamin D was not effective in the subgroup of patients with low serum levels (<20 ng/mL) of total 25(OH)D at baseline, contrary to our expectation that vitamin D would be effective only in the subgroup with low total 25(OH)D [4]. However, in this post hoc study, we demonstrated that vitamin D supplementation may be effective only in cancer patients with low bioavailable 25(OH)D levels.…”
Section: Discussioncontrasting
confidence: 70%
“…This study was a post hoc analysis of the AMATERASU trial conducted in Japan. Details of the study have been previously reported [4]. Briefly, 417 patients with digestive tract cancer from the esophagus to the rectum participated in a randomized, double-blind, clinical trial to compare the effects of vitamin D3 supplements (2000 IU/day) and placebo on RFS and OS at an allocation ratio of 3:2, at the International University of Health and Welfare Hospital (Ohtawara, Tochigi prefecture, Japan) between January 2010 and February 2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With total cancer incidence as the outcome, one of these meta-analyses combined data from 8 prospective cohort studies (70,018 participants and 7511 events) (13). The summary relative risk (RR) estimate of the highest 25(OH)D category compared to the lowest was 0.86 (95% confidence interval (CI): 0.73-1.02), indicating a marginal relationship in the inverse direction, with a significant between-study heterogeneity (I 2 =70.8%).…”
Section: Cancer Incidencementioning
confidence: 99%
“…A recent meta-analysis had total cancer mortality as the outcome (13). This report combined data from 16 prospective cohort studies on 101,794 participants without cancer at baseline, 8729 of whom had a cancer-related death.…”
Section: Cancer Mortalitymentioning
confidence: 99%